2014
DOI: 10.1002/anie.201407394
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium‐Catalyzed Cyclization of Diynes with Nitrones: A Formal [2+2+5] Approach to Bridged Eight‐Membered Heterocycles

Abstract: N-aryl-substituted nitrones were employed as five-atom coupling partners in the rhodium-catalyzed cyclization with diynes. In this reaction, the nitrone moiety served as a directing group for the catalytic C-H activation of the N-aryl ring. This formal [2+2+5] approach allows rapid access to bridged eight-membered heterocycles with broad substrate scope. The results of this study may provide new insight into the chemistry of nitrones and find applications in the synthesis of other heterocycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 55 publications
2
31
0
Order By: Relevance
“…Thep referential formation of 3r,h aving an electron-rich substituent, implies that the slow hydrogen abstraction might occur after the electrophilic attack of palladium(II) on the aromatic ring in the CÀHa ctivation process. [18] Moreover, reacting the palladacycle complex 4,w hich was generated from 1a by palladium(II)-mediated CÀHb ond cleavage, [15a] with an equal molar amount of 2a successfully led to 3a in 93 %y ield (Scheme 2c), thus providing solid evidence to support afree-amine-directed C À Hactivation mechanism for the title transformation. Finally,t wo control reactions were performed, and the experimental data revealed that 3a was not formed from 5 by ap ossible amination/oxidation sequence (Scheme 2d), [16a] but generated through the tautomerization of its enamine-counterpart 6 (Scheme 2e).…”
Section: Methodsmentioning
confidence: 96%
“…Thep referential formation of 3r,h aving an electron-rich substituent, implies that the slow hydrogen abstraction might occur after the electrophilic attack of palladium(II) on the aromatic ring in the CÀHa ctivation process. [18] Moreover, reacting the palladacycle complex 4,w hich was generated from 1a by palladium(II)-mediated CÀHb ond cleavage, [15a] with an equal molar amount of 2a successfully led to 3a in 93 %y ield (Scheme 2c), thus providing solid evidence to support afree-amine-directed C À Hactivation mechanism for the title transformation. Finally,t wo control reactions were performed, and the experimental data revealed that 3a was not formed from 5 by ap ossible amination/oxidation sequence (Scheme 2d), [16a] but generated through the tautomerization of its enamine-counterpart 6 (Scheme 2e).…”
Section: Methodsmentioning
confidence: 96%
“…In 2013 we reported the first catalytic C−H activation of nitrones . Later, we and others realized their couplings with alkenes, alkynes, diazo compounds, and arenes under redox‐neutral conditions, where the role of the nitrone is limited to its oxidizing or electrophilic properties in post‐coupling transformations . Of note, although nitrones are typical 1,3‐dipoles, integration of both C−H activation and dipolar addition has not been realized and these two areas evolved separately.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, the same group used diazo compounds instead of alkynes coupling partners to give access to N-hydroxyindolines under a similar catalytic system [64]. Nitrones as redox-neutral directing group are broadly applied in transition-metal-catalyzed C-H activation/coupling with π-system [61,62]. In 2015, Chang and co-workers developed a Rh(III)catalyzed coupling reaction between arylnitrones and alkynes without the requirement for external oxidant, where Rhodium catalyst not only operates in the C−H bond activation but also evolve Oatom transfer process.…”
Section: Indole Derivativesmentioning
confidence: 99%